Implementing Implementasi Mediasi sebagai Strategi Manajemen Konflik: Studi Kasus Penanganan Konflik Mahasiswa Papua di Unila oleh Kepolisian (Polri) - Naomy Chika Anjani; Prisa Intan Nuraini; Sasmita Dinikencono; Nailatull Izzah Purwandani; Ulul Azmi Vierannanda; Virgiawan Mega Putranto; Saliman Saliman; Yumi Hartati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2026)
Social conflict is a process of dispute that occurs between individuals or groups due to differences in perspectives, interests, or objectives. Conflict arises when one party feels disadvantaged, resulting in tension within social relationships. One form of social conflict in higher education involves Papuan students, which is often influenced by communication misunderstandings and intergroup stereotypes. This study aims to analyze the implementation of mediation as a conflict management strategy in handling the case involving Papuan students at the University of Lampung (Unila) by the Indonesian National Police (Polri). This research employs a qualitative approach using a literature study (library research) method. Data were collected through the review of various scholarly sources, including books, journal articles, official documents, and relevant online sources. The collected data were analyzed using descriptive qualitative analysis to examine the role of mediation in conflict resolution and its effectiveness as a conflict management strategy. The findings indicate that mediation can serve as an effective approach to fostering communication, reducing tensions between conflicting parties, and promoting peaceful and sustainable conflict resolution.